Health Education on Physical Changes in the Menopause in Jatinom Village, Kanigoro Blitar - Agustina, Ika; Choirunnisa, Miftah (STIKes Patria Husada Blitar, 2020)
The changing of menopause times often cause discomfort or anxiety. Women who were initially active in various activities in the community can be disrupted because of various complaints caused by changes in menopause, it will be exacerbated if women do not realize that sigh are caused by physical changes during menopause. The importance of information for older women, especially women aged 48-60 years is given medical education through enlightenment on physical changes at menopause. By this health education, mothers understand better in facing the physical changes they experience. The results of the questionnaire given to mothers found that 10 menopause mothers (83%) did not know the physical changes experienced and 2 menopause mothers (17%) experienced changes that occurred in the mother's body. Providing good and correct education in menopause is very much needed, not just once but it must be repeated, for example, to continue to participate in the elderly posyandu activities so that mothers are aware and fell comfort with their conditions